2003
DOI: 10.1523/jneurosci.23-08-03278.2003
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine/Paracrine Activation of the GABAAReceptor Inhibits the Proliferation of Neurogenic Polysialylated Neural Cell Adhesion Molecule-Positive (PSA-NCAM+) Precursor Cells from Postnatal Striatum

Abstract: GABA and its type A receptor (GABA A R) are present in the immature CNS and may function as growth-regulatory signals during the development of embryonic neural precursor cells. In the present study, on the basis of their isopycnic properties in a buoyant density gradient, we developed an isolation procedure that allowed us to purify proliferative neural precursor cells from early postnatal rat striatum, which expressed the polysialylated form of the neural cell adhesion molecule (PSA-NCAM). These postnatal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
173
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(182 citation statements)
references
References 76 publications
(84 reference statements)
8
173
1
Order By: Relevance
“…Neuroblasts in the SEZ are sensitive to benzodiazepines [7,8]. As we had found that PS þ /EGFR high and PS þ /EGFR low cells express a similar range of GABA A R subunits (Supporting Information Fig.…”
Section: Gaba a Rs Activation Increases The Proliferation Of Egfr Higmentioning
confidence: 80%
See 1 more Smart Citation
“…Neuroblasts in the SEZ are sensitive to benzodiazepines [7,8]. As we had found that PS þ /EGFR high and PS þ /EGFR low cells express a similar range of GABA A R subunits (Supporting Information Fig.…”
Section: Gaba a Rs Activation Increases The Proliferation Of Egfr Higmentioning
confidence: 80%
“…GABA signaling exerts a complex regulation also in the adult subependymal zone (SEZ) where neuroblasts and glial fibrillary acidic protein (GFAP)-expressing cells, which include stem cells as well as astrocytes, regulate ambient GABA levels, by mediating its nonsynaptic release and uptake, respectively [5]. In turn, GABA A R activation downregulates neuroblast proliferation and migration [6][7][8]. Activation of GABA A R also inhibits the proliferation of GFAP-expressing cells in the adult niche [5].…”
Section: Introductionmentioning
confidence: 99%
“…GABA can be released via phasic release through Ca 2+ -dependent vesicular exocytosis from neurons and by tonic release, independent of action potentials and vesicles, by permeation through the Bestrophin 1 anion channel in neurons and glia (39). Neuroblasts within the germinal zone release GABA tonically, which acts on GFAP + progenitors in the SVZ, negatively affecting proliferation (10,40,41). Bestrophin 1 gates GABA already at very low (i.e., resting) intracellular Ca 2+ concentrations (100 nM) but increases release with increasing Ca 2+ concentrations (39).…”
Section: Discussionmentioning
confidence: 99%
“…GABA plays an important signaling role in developmental processes, such as embryonic cell proliferation and migration 12-17 as well as regulating the migratory speed and production of neuroblasts in postnatal SVZ 11,18 . To support GABAergic signaling from neuroblasts to GFAP-expressing cells, the expression of GABA receptors in GFAP-expressing cells has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%